Uniqueness for the electrostatic inverse boundary value problem with piecewise constant anisotropic conductivities. (22nd November 2017) - Alessandrini, Giovanni; de Hoop, Maarten V; Gaburro, Romina
Abstract: We discuss the inverse problem of determining the, possibly anisotropic, conductivity of a body Ω ⊂ R n when the so-called Neumann-to-Dirichlet map is locally given on a non-empty curved portion Σ of the boundary ∂ Ω . We prove that anisotropic conductivities that are a priori known to be piecewise constant matrices on a given partition of Ω with curved interfaces can be uniquely determined in the interior from the knowledge of the local Neumann-to-Dirichlet map.